Insights into the role of bioactive plants for lambs infected with Haemonchus contortus parasite - Komáromyová, Michaela; Petrič, Daniel; Demčáková, Klára; Leško, Matej; Čobanová, Klaudia; Babják, Michal; Königová, Alžbeta; Kuzmina, Tetiana; Ślusarczyk, Sylwester; Fortuna, Paulina Izabela; Łukomska, Anna; Sidoruk, Pola; et al. (Frontiers in Veterinary Science, 2025)
Bioactive plants provide therapeutic and prophylactic effects to ruminants. We determined the effect of grazing on natural meadow grassland enriched with experimentally sown chicory (Cichorium intybus) on parasitological status, pasture larval infectivity, antioxidant parameters, and the histology of abomasal tissue in lambs experimentally infected with the parasitic gastrointestinal nematode (GIN) Haemonchus contortus. We also qualitatively identified the main polyphenols in the meadow grassland and phenolic metabolites in the feces of the lambs. Sixteen lambs were orally infected with approximately 5,000 infective larvae (L3) of H. contortus. The lambs were divided into two groups: lambs grazing on a plot consisting exclusively of meadow pasture which serves as control group and lambs grazing on a plot where approximately 25% of a meadow grassland was reclaimed with chicory. The experimental period was 144 days. The number of eggs per gram (EPG) of feces was quantified on D21, D34, D48, D62, D76, D89, D103, D118, D131, and D144 post-infection. Pasture contamination with H. contortus L3 was examined. EPG in both groups of lambs was highest at D34. Egg shedding was significantly lower in both groups from D48 onwards, with a reduction of >95% from D103 onwards. Pasture contamination with L3 was highest at D41 but was then significantly lower in both groups. The total antioxidant capacity, the activity of glutathione peroxidase and the concentration of malondialdehyde in the serum changed significantly during the experiment (p < 0.003, < 0.001, and < 0.016, respectively). At least 54 species of meadow plants were identified on both pasture plots; plant bioactive compounds identified were mainly phenolic acids, flavonoids, and glucosides. Phenolic metabolites (e.g., coumaric acid, chicory acid, salvigenin, and esters of gallic acid) were identified in the feces of the lambs. In some lambs, the morphological observation identified small histopathological changes in the abomasal tissues typical of hemonchosis. Both the natural meadow pasture and the pasture enriched with experimentally sown chicory slowed the dynamics of GIN infection and pasture contamination with L3 by mobilizing the antioxidant defensive system and gradually increasing the resistance of the infected lambs, probably due to the beneficial effects of plant bioactive substances.